2021
DOI: 10.1108/jqme-01-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Toward a framework for a maintenance architecture

Abstract: PurposeThis paper aims to investigate how the product architecture and service architecture methodology can be applied in strategic maintenance optimization to reduce the non-value-adding variance of maintenance, decrease the complexity and ensure alignment in maintenance practices in asset-intensive companies. The proposed maintenance architecture model will make it possible to make data-driven decisions regarding how the equipment should be grouped and maintained.Design/methodology/approachThe research appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…The study started with an observation of a lack of overview of the maintenance process in a case company. As the study by Sigsgaard et al (2021) had shown, such an overview could be gained through a maintenance architecture mapping of the aspects equipment, action, and process. However, mapping especially the action view became difficult as the amount of data was too big and difficult to compare.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study started with an observation of a lack of overview of the maintenance process in a case company. As the study by Sigsgaard et al (2021) had shown, such an overview could be gained through a maintenance architecture mapping of the aspects equipment, action, and process. However, mapping especially the action view became difficult as the amount of data was too big and difficult to compare.…”
Section: Methodsmentioning
confidence: 99%
“…However, where maintenance differs from services is in the recipient of the delivered value. In maintenance the asset owner who needs a safe production that functions within the given specifications is the recipient of value (K. V. Sigsgaard et al, 2021). In services the recipient is typically an entity outside the company in the form of a client or customer (Løkkegaard et al, 2016).…”
Section: Technology Architectures and Modularizationmentioning
confidence: 99%
See 3 more Smart Citations